Antifungal activity of ethanolic extract of Syzygium polyanthum (Wight) Walp. leaves extract against several types of filamentous fungi and Candida species - Wong, Jun Xian; Ramli, Suzita; Rukayadi, Yaya; Khir Juhari, Nik Khairunnisa; Radu, Son; Abd Wahid, Nurul Bahiyah (Penerbit Universiti Putra Malaysia, 2022)
The aim of this study was to determine the antifungal activity of Syzygium polyanthum extract against opportunistic filamentous fungi and pathogenic Candida species by using standard method of Clinical and Laboratory Standard Institute (CLSI). All fungi were susceptible to S. polyanthum extract with minimum inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) ranged between 0.63 - 1.25 mg/mL, 1.25 - 5.0 mg/mL, respectively. Moreover, the extract of S. polyanthum inhibited more ≥ 90% conidia germination of tested filamentous fungi. Killing time of S. polyanthum extract on C. albicans, C. glabrata, C. parapsilosis and C. krusei was fast acting where it showed 3 log10 CFU/mL reduction at 4× MIC in 4 h. Morphology changes had been viewed on treated strains included changing in cell wall thickness, rupture and leakage of the cells cytoplasm. The maximum cell constituents release was observed at 4× MIC for 72 h incubation for A. niger with an absorbance 0.381 whereas 0.435 for C. albicans after 4 h incubation at 4× MIC. Therefore, results suggest that S. polyanthum extract had antifungal activity and might be able to develop as a natural antifungal agent.